Between Feminism and Materialism - Howie, G. author. aut Link
XI, 268 p.
Keywords: In her latest book, Gillian Howie offers a bold new way to make sense of the relationship between feminist theory and capitalism. This exciting combination of existentialism, phenomenology, and critical theory delivers a proactive feminism ready to respond to the challenges presented by our thoroughly modern times.